High-voltage switchgear and controlgear. Seismic qualification for metal enclosed and solid-insulation enclosed switchgear and controlgear assemblies for rated voltages above 1 kV and up to and including 52 kV Part 210, (28th February 2013) - British Standards Institution,
No abstract available